2004
DOI: 10.1007/s00418-004-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of human tenocytes in high-density culture

Abstract: Limited supplies of tendon tissue for use in reconstructive surgery require development of phenotypically stable tenocytes cultivated in vitro. Tenocytes in monolayer culture display an unstable phenotype and tend to dedifferentiate, but those in three-dimensional culture may remain phenotypically and functionally differentiated. In this study we established a three-dimensional high-density culture system for cultivation of human tenocytes for tissue engineering. Human tenocytes were expanded in monolayer cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 41 publications
3
94
1
2
Order By: Relevance
“…Embedded in this network of fibrils are tenocytes. These cells produce all components of the extracellular matrix and consequently play an important role in the structure and function of the tendon [16,17]. Cell-cell and cell-matrix interactions are mediated via transmembrane signal transduction receptors such as 1 -integrins.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded in this network of fibrils are tenocytes. These cells produce all components of the extracellular matrix and consequently play an important role in the structure and function of the tendon [16,17]. Cell-cell and cell-matrix interactions are mediated via transmembrane signal transduction receptors such as 1 -integrins.…”
Section: Introductionmentioning
confidence: 99%
“…9,20 When the tendon fibers have been altered by severe chronic degeneration, primary repair is not a sure method of treatment and re-tear rates are discouraging. In fact, the poor tissue quality creates difficulties in achieving secure fixation with primary repair.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the present study, cells derived from tendons were used and were characterized by means of cell morphology and ECM protein production as performed in many other studies. 12,13,21,23,26,29,30,33,35 Moreover, in our study in order to maintain the phenotype we used the explant technique, in which cells are permitted to grow from small fragments of tissue instead of enzymatic digestion that affects cell membrane and destroys the cell-cell and cell-matrix relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental studies have demonstrated that cultured cells can be switched between different fates including growth, differentiation, apoptosis, directional motility or different stem cell lineages, by modulating cell shape. (Barkhausen T et al 2003) (Brown RA et al 1998) (Wang JH et al 2004) (Schulze-Tanzil G et al 2004) Externally applied cyclic strain under in vitro conditions has enormous effects on various functions of tenocytes, such as their metabolism, proliferation, orientation and matrix deposition (Screen HRC et al 2005) (Yamamoto E et al 2005) Kessler et al (Kessler et al 2001) demonstrated that collagen fibres and tendon cells can be oriented along the direction of the stress and can upregulate synthesis of tissue inhibitor matrix metalloproteinases-1 and -3 as well as of collagen type I, the main component of tendinous extracellular matrix. It is known that cyclic strain can affect cell morphology and induce uniaxial cellular alignment.…”
Section: Tendon Engineering By the Application Of Mechanical Loadmentioning
confidence: 99%